L-carnitine in complex treatment of neurocirculatory hypotension in children and adolescents - N.V. Orlova; O.V. Mikhaylova; T.V. Zakharova ("Paediatrician" Publishers LLC, 2011)
The article describes main etiological and pathogenetic factors of neurocirculatory dystonia (NCD). The most frequent type of NCD is arterial hypotension. Arterial hypotension is main cause of energetic deficiency and, as a result, hypoxemia of tissues. L-carnitine plays significant role in formation of energetic compounds; consequently administration of L-carnitine to children and adolescents with neurocirculatory hypotension is reasonable. Treatment with L-carnitine results in beneficial effect on subjective symptoms of the disease, functional parameters of vegetative nervous system and vagus-dependent electrocardiologic parameters. The results of a work allow optimization of NCD treatment in children and adolescents. Key words: children, adolescents, neurocirculatory dystonia, L-carnitine, treatment.